Filamin A regulates caspase-3 cleavage in platelets in a protein kinase C (PKC)-dependent manner. Issue 22 (30th November 2022) - De Silva, Enoli; Devine, Dana V.; Jan, Eric; Roskelley, Calvin D.; Kim, Hugh
Abstract : Apoptosis is a critical process for the maintenance of cell populations, and involves mitochondrial depolarization, the sequential cleavage of caspase-9 and -3, followed by the externalization of phosphatidylserine (PS) on the plasma membrane. The actin cytoskeleton and its accessory proteins are known regulators of apoptotic signaling in nucleated cells but their roles in platelet apoptosis are undefined. Filamin A (FLNA) is a ubiquitously expressed actin-crosslinking protein that also serves as an intracellular signaling scaffold. Here we used platelets from mice with a platelet-specific FLNA deficiency ( Flna fl /Y, Pf4-cre/+, termed platelet-specific knockout) to test the role of FLNA in platelet apoptosis. Treatment with the BH3-mimetic drug ABT-737 induced caspase-3 cleavage and PS exposure in platelets from floxed mice ( Flna fl /Y, termed control) but these effects were essentially abrogated in FLNA-null platelets (platelet-specific knockout). Protein kinase C (PKC), a known FLNA ligand, was also activated by ABT-737, and PKC's phosphorylation of its downstream substrates was attenuated in FLNA-null platelets. The PKC inhibitor bisindolylmaleimide (BIM) also reduced caspase-3 cleavage, thus essentially phenocopying the FLNA-null platelets. Notably, the caspase-3 cleavage defect in FLNA-null platelets was rescued by the PKC-activating phorbol ester PMA, suggesting that FLNA and PKC share a common pathway in regulating platelet apoptosis. Mitochondrial depolarization and caspase-9 cleavage were unaffected by BIM treatment, suggesting that PKC specifically controls the downstream caspase-3 point of the pro-apoptotic signaling pathway. These data point to a novel role for FLNA in the regulation of platelet apoptosis, thus providing an improved understanding of how circulating platelet counts are maintained.